2020
DOI: 10.3390/ijms22010045
|View full text |Cite
|
Sign up to set email alerts
|

Initiators of Classical and Lectin Complement Pathways Are Differently Engaged after Traumatic Brain Injury—Time-Dependent Changes in the Cortex, Striatum, Thalamus and Hippocampus in a Mouse Model

Abstract: The complement system is involved in promoting secondary injury after traumatic brain injury (TBI), but the roles of the classical and lectin pathways leading to complement activation need to be clarified. To this end, we aimed to determine the ability of the brain to activate the synthesis of classical and lectin pathway initiators in response to TBI and to examine their expression in primary microglial cell cultures. We have modeled TBI in mice by controlled cortical impact (CCI), a clinically relevant exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…While we observed a drop of Tmem119 protein levels, Tmem119 gene expression increased in the contused area, with a micro topical distribution of its overexpression, mirroring that of C1q, an inflammatory gene associated with microglia activation and synaptic pruning after TBI (Krukowski et al, 2018;Ciechanowska et al, 2021). Overexpression of Tmem119 was previously reported after 4 days, and to a minor extent, 7 days after TBI in RNA extracts of the cortex, striatum, and hippocampus ipsilateral to the contusion, along with the overexpression of a wide spectrum of cellular markers for neutrophils, CD8+ T cells, astroglia, and microglia/macrophages (Ciechanowska et al, 2021). The observation that Tmem119 protein levels clearly decreased in active microglia in the TBI brain, while the mRNA increased could be due either to the impaired Tmem119 translation, possibly due to posttranscriptional modifications causing reduced Tmem119 transcript stability, or to the enhanced protein degradation.…”
Section: Discussionmentioning
confidence: 67%
“…While we observed a drop of Tmem119 protein levels, Tmem119 gene expression increased in the contused area, with a micro topical distribution of its overexpression, mirroring that of C1q, an inflammatory gene associated with microglia activation and synaptic pruning after TBI (Krukowski et al, 2018;Ciechanowska et al, 2021). Overexpression of Tmem119 was previously reported after 4 days, and to a minor extent, 7 days after TBI in RNA extracts of the cortex, striatum, and hippocampus ipsilateral to the contusion, along with the overexpression of a wide spectrum of cellular markers for neutrophils, CD8+ T cells, astroglia, and microglia/macrophages (Ciechanowska et al, 2021). The observation that Tmem119 protein levels clearly decreased in active microglia in the TBI brain, while the mRNA increased could be due either to the impaired Tmem119 translation, possibly due to posttranscriptional modifications causing reduced Tmem119 transcript stability, or to the enhanced protein degradation.…”
Section: Discussionmentioning
confidence: 67%
“…Specifically, an analysis of complement genes extracted from an RNAseq dataset acquired from the cortex at 1 day post CCI (GSE79441) [ 45 ], revealed upregulation of C1qa-c , C3ar1 , Itgam, Itgax , Cd44 , CD93 , Ager and Serping1 , and downregulation of regulatory Csmd1 , which is in line with our data. Moreover, a recent qRT-PCR study characterizing the regional expression of classical and lectin initiators up to 5 weeks after CCI reported the upregulation of C1q , C1s , and Fcnb , and the absence of MBL dysregulation [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous high-throughput studies have analyzed gene and protein expression in various experimental models of TBI, both acutely and chronically after injury [ 4 7 ]. Notably, local and systemic changes in the level of complement system components were consistent and of high magnitude across the various injury models at specified time points.…”
Section: Introductionmentioning
confidence: 99%
“…One recent clinical study showed that elevated serum C1q levels were significantly correlated with traumatic severity and could serve as an independent prognostic factor for long-term outcomes after TBI [73]. After TBI, microglia and neurons were the primary source of C1q [74,75]. The increased expression of C1q might lead to neuron loss and chronic neuroinflammation and correlate with sleep spindle loss and epileptic spikes.…”
Section: Discussionmentioning
confidence: 99%